Super-resolution reconstruction of electrical impedance tomography images. (July 2018) - Borsoi, Ricardo Augusto; Aya, Julio Cesar Ceballos; Costa, Guilherme Holsbach; Bermudez, José Carlos Moreira
Abstract: Electrical Impedance Tomography (EIT) systems are becoming popular because they present several advantages over competing systems. However, EIT leads to images with very low resolution. Moreover, the nonuniform sampling characteristic of EIT precludes the straightforward application of traditional image super-resolution techniques. In this work, we propose a resampling based Super-Resolution method for EIT image quality improvement. Results with both synthetic and in vivo data indicate that the proposed technique can lead to substantial improvements in EIT image resolution, making it more competitive with other technologies.